Analisis Pengaruh Kualitas Pelayanan terhadap Kepuasan Konsumen RS St. Elisabeth Semarang - Khasanah, Imroatul; Pertiwi, Octarina Dina (Jurnal Ilmu Ekonomi ASET, 2010)
The purpose of this research was for analyzing 5 assessments: 1. Effect on thetangible against consumer satisfaction, 2. Effect on reliability against customer satisfaction,3. Effect on responsiveness on customer satisfaction, 4. Effect on guarantee & certainty againstcustomer satisfaction, 5. Effect on empathy against customer satisfaction. This research hasbeen done with samples taken in random with consideration that the population was verylarge in numbers, as it wasnât possible for the surveyor to cover the whole present population,so a representative was formed. Samples in this survey were only a part of the whole communityof the city of Semarang that used the services of St. Elisabeth Hospital. Result of this surveyshows that these 5 assessments were accepted. The result was, there was a positive andsignificant relation between tangible of St. Elisabeth hospital, reliability of St. Elisabeth hospitalin handling consumer, responsiveness of St. Elisabeth hospital, guarantee & certainty givenby St. Elisabeth hospital, empathy against customer satisfaction. This was proved by test Fwhere the value of significance was 0,000, the coefficient of determination on satisfactionshown by Adjusted R Square was 0,716 that means the customer satisfaction was 71,6% affectedby variable of tangible, reliability, responsiveness, guarantee and empathy. Whereas, the restof the 28,4% was affected because other variables were not checked thoroughly by researchers.Keywords: customer satisfaction, tangible, reliability, responsiveness, assurance and empathy.